2017
DOI: 10.1016/j.carbpol.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathways during oxidation of cereal β-glucans

Abstract: Oxidation of cereal β-glucans may affect their stability in food products. Generally, polysaccharides oxidise via different pathways leading to chain cleavage or formation of oxidised groups within the polymer chain. In this study, oxidation pathways of oat and barley β-glucans were assessed with different concentrations of hydrogen peroxide (HO) or ascorbic acid (Asc) with ferrous iron (Fe) as a catalyst. Degradation of β-glucans was evaluated using high performance size exclusion chromatography and formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(31 reference statements)
1
5
1
Order By: Relevance
“…Interestingly, however, the two oxidation conditions exhibited different proportions regarding the more diagnostic cross-ring cleavage products such as Ara- and Ery-2AB (Figure 7B ). This contrasts results from Mäkelä et al ( 2017 ), who also observed arabinose from OBG and BBG oxidation with H 2 O 2 (10–70 mM) by HPAEC-PAD after hydrolysis with lichenase/β-glucosidase, but not for samples oxidized with AH 2 (10–70 mM). This underlines the sensitivity of our method with 2-AB labeling and UPLC-MS analysis that allowed detection of cross-ring cleavage products even from a very mild oxidation.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…Interestingly, however, the two oxidation conditions exhibited different proportions regarding the more diagnostic cross-ring cleavage products such as Ara- and Ery-2AB (Figure 7B ). This contrasts results from Mäkelä et al ( 2017 ), who also observed arabinose from OBG and BBG oxidation with H 2 O 2 (10–70 mM) by HPAEC-PAD after hydrolysis with lichenase/β-glucosidase, but not for samples oxidized with AH 2 (10–70 mM). This underlines the sensitivity of our method with 2-AB labeling and UPLC-MS analysis that allowed detection of cross-ring cleavage products even from a very mild oxidation.…”
Section: Resultscontrasting
confidence: 98%
“…Apart from threatening the molecular integrity of BG and its health benefits (Wood et al, 2000 ; Wolever et al, 2010 ; Regand et al, 2011 ), deliberate incorporation of new functional groups through oxidation has also been reported to change BG's technological (Lee et al, 2011 ) and health promoting properties (Park et al, 2009 ), providing great potential to influence BG functionality. Hence, cereal BG oxidation has been the focus of numerous studies employing various analytical techniques to investigate the radical reaction (ESR), to characterize the products (NMR/FT-IR), and monosaccharide composition (HPAEC-PAD), to quantify carbonyl or carboxylate groups (titration, fluorescent labeling), and to determine the change in bulk properties (rheology, M w distribution, aggregation; Kivelä et al, 2010 , 2011 , 2012 ; Faure et al, 2012 , 2013a , 2014 ; Mäkelä et al, 2015 , 2017 ). On a molecular level, indirect detection of oxo-products from HO • -mediated degradation of barley BG was reported by Iurlaro et al ( 2014 ), employing reductive tritium labeling followed by enzymatic or acid catalyzed hydrolysis and analysis by paper- and thin-layer chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds well with the results of Faure et al (2012), which showed faster formation of hydroxyl radicals in BBG than in OBG during the first 6 h of oxidation and similar contents of hydroxyl radicals in both BBG and OBG after 24 h of oxidation. The difference in the effectiveness of hydrogen peroxide to oxidatively degrade BBG85 and OBG85 was already shown in our former study (Mäkelä et al, 2016), where significantly higher Mw decrease was observed in BBG85 when the oxidative degradation of BBG and OBG were compared. According to Wang, Maina, Ekholm, Lampi, & Sontag-Strohm (2016), this difference was caused by a variation in the phytate content of these commercial β-glucans.…”
Section: Viscosities and Hysteresis Of Barley And Oat β-Glucans Dissosupporting
confidence: 62%
“…Besides enzymatic and acid hydrolysis, also oxidation has been shown to cause degradation of βglucan (Faure, Andersen, & Nyström, 2012;Kivelä, Gates, & Sontag-Strohm, 2009a;Kivelä, Nyström, Salovaara, & Sontag-Strohm, 2009b;Kivelä, Henniges, Sontag-Strohm, & Potthast, 2012;Mäkelä, Sontag-Strohm, & Maina, 2015, Mäkelä et al, 2016. The initiation of β-glucan oxidation can occur in the presence of reactive oxygen species (ROS), the hydroxyl radical (•OH) being the most reactive one.…”
Section: Introductionmentioning
confidence: 99%
“…They can be formed through various pathways such as Fenton reaction in the presence of endogenous hydrogen peroxide and ferrous iron (H 2 O 2 + Fe 2+ → Fe 3+ +·OH + OH − ). Hydroxyl radicals can attack the ␤-glucan leading to significant viscosity and molecular weight decrease, formation of carbonyl groups along the ␤-glucan chain and the release of formic acid (Kivelä, 2011;Mäkelä et al, 2017). Fenton reaction can be initiated by the presence of ascorbic acid which is a common additive in food.…”
Section: Introductionmentioning
confidence: 98%